Economic aspects of the integration of Bosnia and Herzegovina with the European Union in the second decade of the 21st century - Monika Szynol (Przegląd Europejski, 2020)
At the end of the second decade of the 21st century the European Union (EU) – presenting a new strategy of enlargement policy, organising an official summit of the state leaders and devoting to potential accessions the meeting of the Council of the EU – recalled that the future of the Western Balkans lies in the EU. Therefore, there is a reasonable question: whether the intensification of the EU’s enlargement policy will affect favourably Bosnia and Herzegovina, a state considered as a potential candidate for the membership since 2003? Basing on (inter alia) official documents issued by the EU institutions, macroeconomic data and in relation to the EU’s policy towards the Western Balkans region, it is worthwhile to suppose, that – despite numerous (political, economic, social) deficits and weaknesses – Bosnia and Herzegovina, which applied for membership in the EU in 2016, will receive the status of an official candidate country soon (in the thir d decade of the 21st c entury).